Pengaruh Ethical Leadership, Self-Efficacy, dan Emotional Intelligence Terhadap Perilaku Kerja Inovatif Pada Karyawan Bank - Regita Dwicahya Swarpandhani; Lucy Warsindah (STIE AMKOP, 2023)
This study aims to analyze the effect of ethical leadership, self-efficacy, and emotional intelligence on innovative work behavior among employees of a state-owned bank. This research method uses quantitative methods. The sampling procedure used is non-probability sampling with purposive sampling technique. Data was obtained by distributing questionnaires to 220 employees of one of the state-owned banks. The data analysis method used is univariate analysis using descriptive statistics and multivariate analysis using multiple regression analysis tests with the help of SPSS 26 software. The results of this study indicate that ethical leadership has a positive and significant effect on innovative work behavior, self-efficacy has a positive and significant effect on innovative work behavior, and emotional intelligence has a positive and significant effect on innovative work behavior. Based on research results, to increase innovative work behavior can be done through increasing the role of self-efficacy which can be obtained through internal training which aims to develop employee skills and knowledge so that they are able to overcome various at work.